Technology to Facilitate Telehealth in Applied Behavior Analysis - Zoder-Martell, Kimberly A. (Behav Anal Pract, 2020)
In light of the COVID-19 pandemic, many behavior analysts have temporarily transitioned to providing services using a telehealth model. This has required them to rapidly shift their treatment modality. The purpose of this article is to provide a review of some available technologies to support telehealth that will allow behavior analysts to conduct direct observation from a remote location. We reviewed 3 technologies that can be used for telehealth: (a) web cameras, (b) Swivl, and (c) telepresence robots. Features of each of these technologies are compared, and the benefits and drawbacks of each are reviewed. Sample task analyses for using each technology are also provided. Finally, tips for using telehealth with families are provided.